CHALLENGES FACED BY FISHERS AT IGBEDI CREEK, WILBERFORCE ISLAND, BAYELSA STATE, NIGERIA - ADEYEMO, A. O (Nigerian Journal of Fisheries, 2011)
A study was carried out on the challenges of fishers of the Igbedi creek area of River Nun using questionnaire and informal interviews. A total of 120 questionnaires were administered; only 92 were successfully recovered. Igbedi Creek is a distributary of River Nun, a tributary of River Niger. Igbedi Creek fishery is characterised by artisanal or rather subsistence operations, low catches, high water turbidity with clay suspensions due to dredging and construction works. The fishery is traditionally managed with low participation of stakeholders. The challenges ranked on a score of 4 points were: lack of government intervention 4, inadequate fishing input 3.25, poor marketing structure 2, low income from fishing 1.95, poor catches 1.90, degradation of ecosystem 1.55, destruction of gear 1.40 and old age 1.25. Gears commonly used by fishers were nets, hooks and lines and traps of all sorts and shapes The prospects of Igbedi Creek fisheries can be enhanced by improved political will, participation of stakeholders in the management, putting in place structured research and adequate data collection programme. Establishing environmental protection programmes and organized marketing structure will also empower and improve the livelihoods of members’ in communities along the creek.